Micro-volunteering at scale can help health systems respond to emergencies, such as the Covid-19 pandemic - Neil Churchill (The Beryl Institute, 2020)
One of the unprecedented challenges of the Covid-19 pandemic has been to support millions of clinically high-risk individuals who were advised to self-isolate for long periods to reduce the likelihood of infection. The NHS in England issued a mass call for volunteers in March 2020 to help support people who were shielding or vulnerable for other reasons during the lockdown. Three quarters of a million people came forward to aid the health at home experience for these vulnerable individuals by providing friendly telephone calls, help with shopping or collection of medicines or transport to essential hospital appointments. Hospitals also used to scheme to replace older volunteers who had been stood down after Covid-19 risk assessments and to help patients avoid unnecessary trips into their services. As we gained experience of running the scheme, additional tasks were added, such as support for Covid-19 research trials. The approach to ‘micro-volunteering’ at scale has been hugely beneficial and has significantly increased the number and diversity of volunteers supporting the health system. This article describes the scheme and provides an account of achievements over the first wave of Covid-19 in England. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.